Sandy Pylos : an archaeological history from Nestor to Navarino - Davis, Jack L.; Bennet, John, 1957-; Alcock, Susan E. (ACLS Humanities E-Book., 2008)
This book traces the archaeological history of Pylos and surrounding regions in Messenia from the Palaeolithic to the present. Designed as much for general readers and travelers interested in ancient Greece as for scholars, the volume presents the findings of the Pylos Regional Archaeological Project (PRAP), which has intensively studied the region over the past 15 years. The 1998 edition, originally published by the University of Texas Press and widely used as a textbook in undergraduate classes, is reprinted for 2008 with a new preface assessing PRAP's impact and outlining new discoveries in the region.